(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God who made us among the people of Arabic a tongue, then made us among its people a study, then singled us out for the closest sciences to the Holy Quran (Arabic sciences in general, and grammar in particular). Lesson and research have been renewed with other lessons and research, as it is still with the pyramid of time, except for Jeddah.